Answer:
f(-2) = 38
Explanation:
So what you start with is the variable "x" in 3 different places. When you are changing the x variable, you need to plug it into every variable in the equation. Start by doing that and the problem will look like:
f(-2) = 3(-2)^2 - (-2)
Now you can start with either the 3(-2)^2 or the - (-2), but it is better to go from left to right. So simplify the first section:
3 * -2 = -6
-6^2 = -6 * -6 = 36
So now you have:
f(-2) = 36 - (-2)
Then you should know that when you subtract a negative, it turns into addition. So the new problem looks like:
f(-2) = 36 + 2
Aka
f(-2) = 38
Hope this helped!
^_^